Ulkus Kaki Diabetik Sebuah Laporan Kasus - Muhammad Syahrir; Indah Lestari Daeng Kanang; Fadil Mula Putra (NERSMID : Jurnal Keperawatan dan Kebidanan, 2026)
Diabetes mellitus is derived from the Greek word diabetes, meaning to suck through, and the Latin word mellitus, meaning sweet. This case report aims to describe the problems that occurred during the study. The research method used is a descriptive case study report based on medical record data and direct interviews. The results of this case show complications of diabetes mellitus because the patient has a chronic disease course, namely diabetic neuropathy, so the patient is unaware of the wounds on his feet that resulted in diabetic foot ulcers. In this case, the patient's Type 2 DM disease, which he has suffered from for the past 10 years, is not controlled. The patient underwent debridement and routine wound care to prevent further infection, the patient was also given medication according to the results of the patient's supporting examinations. The conclusion is that the most important components in the management of diabetic foot ulcers are metabolic control, vascular control, infection control, pressure control, counseling/education.